2010
DOI: 10.1111/j.1365-2958.2010.07407.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide‐sensitive and ‐insensitive interaction of Bacillus subtilis NsrR with a ResDE‐controlled promoter

Abstract: Summary NsrR is a nitric oxide (NO)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 52 publications
4
53
0
Order By: Relevance
“…4). This result is consistent with the previous in vitro binding data for nasD (13). Association of NsrR with ykuN was reduced 4-fold either during nitrate respiration or by exposure to sperNONOate, indicating that the binding is NO sensitive in vivo, albeit to a lesser extent than that to nasD.…”
Section: No Affects Nsrr Binding In Vivosupporting
confidence: 82%
See 4 more Smart Citations
“…4). This result is consistent with the previous in vitro binding data for nasD (13). Association of NsrR with ykuN was reduced 4-fold either during nitrate respiration or by exposure to sperNONOate, indicating that the binding is NO sensitive in vivo, albeit to a lesser extent than that to nasD.…”
Section: No Affects Nsrr Binding In Vivosupporting
confidence: 82%
“…Our previous study indicated that ResD is involved in transcriptional regulation of all NsrR-controlled genes tested thus far (13). We wondered whether ResD controls NsrR-repressed genes by directly binding to promoter regions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations